Pembangunan jembatan baja ringan lantai komposit beton bertulang dengan perkuatan eksternal stressing di kelurahan Harapan jaya - Andi Indianto; Rikki Sofyan Rizal; Hendrian Budi Bagus Kuncoro (IKIP SILIWANGI, 2023)
Infrastructure development is important in supporting the economic growth of the community, which can be seen from the development of the accessibility of resource production. The people of Bulak Rata Village, RT 002 RW 007, Pondok Rajek Village, Cibinong, are separated by a small river 6 meters wide from Kramat Village, Harapan Jaya Village, Cibinong. Therefore, it is necessary to build a strong bridge so that people can cross safely and comfortably. The contribution that will be made to the Community Service program is to build a Light Steel Bridge with Reinforced Floors with external stressing reinforcement. It is hoped that the construction of this lightweight steel bridge with external stressing can be used for the mobility of local residents. The dimensions of the bridge made are 6m x 1m in size. In the initial stage, namely the manufacture of a light steel bridge frame which is assembled outside the site, after everything is finished and the field conditions have been casting abutments, the light steel bridge frame is mobilized to be placed on top of the abutments. Then proceed with casting the floor plate, where the concrete is made on site using a concrete mixer. When all the work has been completed, all the concrete is cured up to the design age, and after that, the loading test is carried out and continued with the acceptance of the bridge to the surrounding community.